WHAT IS THE DETERMINANTS OF AUDIT QUALITY AT PUBLIC ACCOUNTANT FIRMS IN SOUTH SULAWESI, INDONESIA? (Economic studies journal, 2023)
This study is a quantitative study that aims to determine the impact of auditor skepticism, auditor competence, auditor integrity, and auditor experience on audit quality. The population of this study was the auditors at public accounting firms in South Sulawesi, Indonesia. Then the sample size was determined by 60 respondents using the purposive sampling method, and data was collected by using questionnaires via a google form. The study relied on the descriptive approach and followed the method of descriptive analysis and deductive analysis and using the statistical program (SPSS. v 25). To test the hypotheses, the inferential tests were used, which are the t-test and the f-test at a significant level of 5% (0.05).The results of this study show (1) there is a positive and significant effect between auditor’s skepticism on audit quality; (2) there is a positive and significant effect between auditor’s competence on audit quality; (3) there is a positive and significant effect between auditor’s integrity on audit quality; (4) there is a positive and significant effect between auditor’s experience on audit quality. (5) auditor's skepticism, auditor’s competence, auditor’s integrity, and auditor’s experience hours simultaneously effect on audit quality at public accounting firms in South Sulawesi, Indonesia.
Keywords: skepticism; competence; integrity; experience; audit quality